Comparison Profile of Nutrition Status in Stage V Chronic Kidney Disease Patients Hemodialyzing Using New and Reuse Dialyzer - Yuli Hermansyah; Ika Aulia Kurniasari; Heni Fatmawati (Journal of Agromedicine and Medical Sciences, 2019)
Burn wound healing process consists of three phases of inflammation, proliferation and remodelling. The number of fibroblasts has increased during the proliferation phase. Oxidative stress in burn may disrupt proliferation through TGF-β inhibition, result in decreased number of fibroblasts and poor burn wound healing. Genistein in edamame seeds has anti-inflammatory, antibacterial and antioxidant properties. Edamame contains vitamins A, C, and E which is also have antioxidant properties. Edamame has been suggested to protect burn wound healing from oxidative stress. This study aimed to understand the effectiveness of edamame seed (Glycine max L. Merril) ethanolic extract (ED) to fibroblast count in second degree burn wound healing. This is true experimental research with post test only control group design. The sample of this research was 24 rat models of second degree burn which was made by attaching hot metal (60 ° C) for 5 seconds on the shaved back of the rats. The sample was divided into 6 groups with topical treatment, among others: positive control group (silver sulfadiazine), negative control group (Na CMC 0.5%), group with ED 20%, ED 40%, ED 60%, and ED 80%. Treatment was given for 15 days and skin sample was taken on the 16th day. Observation of the number of fibroblasts was done by taking pictures of histhologic preparations in Hematoxylin and Eosin staining under 400x magnification of light microscope. In one way ANOVA test, significance value of 0.011 (p≤0,05) indicated that there was at least a significant difference between 2 groups. LSD’s post hoc analysis showed that there was a significant difference in the group ED 20, 40, and 60% compared with negative control. Keyword: burn wound healing, vegetable soybean, genistein, fibroblast count, silver sulfadiazine